Observation of large coercivities in radial carbon nanotube structures filled with Fe3C and FeCo single-crystals by viscous boundary layer pyrolysis of ferrocene and cobaltocene. Issue 8 (17th January 2017) - Guo, Jian; Liu, Jiaxun; Lan, Mu; Hu, Yuzhong; Wang, Shanling; Wen, Jiqiu; He, Yi; Gao, Fuhua; Zhang, Xi; Zhang, Sijie; Xiang, Gang; Willis, Maureen A. C.; et al.
Abstract : Viscous boundary layer chemical vapor synthesis is a novel technique that uses the viscous boundary layer between a metallocene/Ar vapor and a rough surface to induce the formation of radial CNT structures highly filled with ferromagnetic materials. Abstract : Viscous boundary layer chemical vapor synthesis is a novel technique that uses the viscous boundary layer between a laminar pyrolysed metallocene/Ar vapor flow and a rough surface to induce the nucleation and growth of radial carbon nanotube (CNT) structures highly filled with ferromagnetic materials. Here we report the synthesis and characterization of radial structures comprising multiwall CNTs filled with large quantities of Fe3 C and FeCo alloys and low quantities of γ-Fe in the forms of small single crystals. Surprisingly high saturation magnetizations up to 80 emu g −1 and a very high coercivity of 1400 Oe at room temperature are found. Such values of magnetization suggest that no room-temperature magnetic interaction is present between γ-Fe and the ferromagnetic crystals in our samples. The presence of such large coercivity values may be associated with the small size of the encapsulated particles which is strongly dependent on the high evaporation temperature of the precursors for fixed pyrolysis temperatures and vapour flow rate. The addition of Cl-species is also considered in the attempt to slow down the growth-rate of the radial CNT-structure and further investigate their growth mechanism.